2022
DOI: 10.3389/fcvm.2022.814326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brachial-Ankle Pulse Wave Velocity on Myocardial Work by Non-invasive Left Ventricular Pressure-Strain in Non-hypertensive and Hypertensive Patients With Preserved Left Ventricular Ejection Fraction

Abstract: ObjectiveData regarding the influence of arterial stiffness on myocardial work (MW) has been scarce. This study was performed to investigate the association between brachial-ankle pulse wave velocity (baPWV) and MW by non-invasive left ventricular pressure–strain in a population of non-hypertensive and hypertensive individuals.MethodsTwo hundred and eight participants (104 hypertensive and 104 non-hypertensive individuals) were prospectively enrolled into the study. All participants underwent conventional echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our study additionally revealed the aortic stiffness index to an independent influencing factor of MW parameters, which persisted even after adjustment for other confounders. The results were consistent with the findings of Duan et al ( 29 ), who reported there to be a significant association between increased arterial stiffness and MW parameters. From another perspective, the relationship between arterial stiffness and MW parameters may facilitate the interpretation of subclinical myocardial function impairment in patients with well-functioning BAV.…”
Section: Discussionsupporting
confidence: 93%
“…Our study additionally revealed the aortic stiffness index to an independent influencing factor of MW parameters, which persisted even after adjustment for other confounders. The results were consistent with the findings of Duan et al ( 29 ), who reported there to be a significant association between increased arterial stiffness and MW parameters. From another perspective, the relationship between arterial stiffness and MW parameters may facilitate the interpretation of subclinical myocardial function impairment in patients with well-functioning BAV.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, hypertensive individuals had significantly higher brachial PWV and significantly lower GLS compared to the normotensive participants but this study did not assess any sex‐based dichotomy (Duan et al, 2022 ). These data agree with studies in male rats with fructose salt sensitive hypertension showing that aortic stiffness is accompanied by a deficit in myocardial shortening as measured by GLS (Duan et al, 2022 ). The present data indicate that these indices are not deranged in females on fructose and high salt diet, coincides with their failure to increase blood pressure on the fructose high salt diet.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, two major meta‐analyses demonstrated that aortic PWV is the most reliable predictor of cardiovascular mortality (Ben‐Shlomo et al, 2014 ; Vlachopoulos et al, 2010 ). A recent study in a mixed population of hypertensive and normotensive individuals showed that those in the highest tertile of brachial PWV had the lowest GLS and the highest proportion of hypertensives (54% vs. 12% and 38% in tertiles 1 and 2, respectively) (Duan et al, 2022 ). Additionally, hypertensive individuals had significantly higher brachial PWV and significantly lower GLS compared to the normotensive participants but this study did not assess any sex‐based dichotomy (Duan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the levels of mean CAVI in their study were 8.9 ± 1.4 and 9.7 ± 1.3, respectively, which obvious higher than our study (8.2 ± 1.3). Although two studies using simple correlation analysis reported that baPWV was significantly associated with GLS in 248 subjects without obvious heart disease 23 and in 208 subjects, 24 these two studies could not provide hypertension‐specific and background‐dependent associations because of small sample size and potential confounders.…”
Section: Discussionmentioning
confidence: 99%